2011
DOI: 10.1007/s11103-011-9861-2
|View full text |Cite
|
Sign up to set email alerts
|

An ethylene response factor OsWR1 responsive to drought stress transcriptionally activates wax synthesis related genes and increases wax production in rice

Abstract: Increasing evidence has revealed the major enzymes-involved in Arabidopsis and maize wax/cutin synthesis; however, there is limited information about the genes-associated with wax/cutin synthesis in rice. Here we report the characterization of an ethylene response factor gene in rice. This rice wax synthesis regulatory gene 1 (OsWR1) is a homolog of Arabidopsis wax/cutin synthesis regulatory gene WIN1/SHN1. Transcript analysis showed that OsWR1 is induced by drought, abscisic acid and salt, and is predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
122
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 60 publications
16
122
0
2
Order By: Relevance
“…It has been proposed that cuticular alkanes confer greater resistance to water diffusion than VLCFAs (13,19). However, total FAs are the major constituents of cuticular wax in rice (16,23), and we obtained similar results in this study. Under drought stress, total FAs, including VLCFAs and LCFAs, were the major components contributing to the increase in the level of wax seen in the WT rice (Fig.…”
Section: Dwa1 Encodes a Megaenzyme-like Protein Highly Conserved Insupporting
confidence: 83%
See 1 more Smart Citation
“…It has been proposed that cuticular alkanes confer greater resistance to water diffusion than VLCFAs (13,19). However, total FAs are the major constituents of cuticular wax in rice (16,23), and we obtained similar results in this study. Under drought stress, total FAs, including VLCFAs and LCFAs, were the major components contributing to the increase in the level of wax seen in the WT rice (Fig.…”
Section: Dwa1 Encodes a Megaenzyme-like Protein Highly Conserved Insupporting
confidence: 83%
“…Overexpression of SHN1/WIN1 caused elevated wax deposition and drought tolerance but unexpectedly increased cuticle permeability and water loss (22). Modulating the expression of rice SHN1/WIN1 homolog wax synthesis regulator 1 (OsWR1) altered wax production and drought tolerance (23). It is unknown how cuticular wax biosynthesis is regulated under drought stress; however, one recent report has shown that MYB96 regulates some wax-biosynthetic genes in Arabidopsis, suggesting it may be required for droughtinduced cuticular wax biosynthesis (13).…”
mentioning
confidence: 99%
“…Previous studies have shown that environmental stresses, such as drought, increase ABA levels, resulting in the increased production of cuticular waxes Seo et al, 2009Seo et al, , 2011Wang et al, 2012). In this study, we conclude that ABA regulation of cuticle formation is an intrinsic aspect of leaf development.…”
Section: Aba Deficiency Has Distinctly Different Effects On Tomato Frsupporting
confidence: 70%
“…While the levels of waxes, and in particular alkanes, were reported to increase following ABA application, no such change in the abundance of cutin monomers was observed, suggesting that other factors trigger changes in the cuticle following water stress . Furthermore, the expression levels of numerous wax biosynthesis-related genes are known to respond to ABA treatment Seo et al, 2009Seo et al, , 2011Wang et al, 2012). For example, the expression of ECERIFERUM1 (CER1), which encodes an enzyme that generates alkanes from very-long-chain acyl-CoA (Bernard et al, 2012), is induced by ABA treatments ).…”
mentioning
confidence: 99%
“…For example, the composition, thickness, and microstructure of the cuticular wax affect water permeability and transport (Svenningsson, 1988;Xu et al, 1995;Buschhaus and Jetter, 2012). Rice DROUGHT-INDUCED WAX ACCUMULATION1, GLOSSY1, and WAX SYNTHESIS REGULATORY GENE1 affect drought tolerance by regulating the deposition or biosynthesis of cuticular wax (Islam et al, 2009;Wang et al, 2012;Zhou et al, 2013;Zhu and Xiong, 2013).…”
mentioning
confidence: 99%